Textures for coding bathymetric data quality sectors on electronic navigational chart displays: design and evaluation. Issue 6 (2nd November 2022) - Kastrisios, Christos; Ware, Colin
ABSTRACT: The Zones of Confidence (ZOC) is a composite data quality indicator used in Electronic Navigational Charts. Accident reports show that failing to account for chart data quality can result in maritime accidents and loss of life. ZOC overlays are intended to help mariners in identifying potential seafloor hazards and in plotting routes safe for the vessel, but a major concern with the ZOC concept has been the utilized symbology with glyphs consisting of stars. Due to its recognized deficiencies, star-symbology has been rejected for use with the successor of ZOC, the Quality of Bathymetric Data (QoBD). This work presents a research effort toward a new QoBD representation. We define the requirements for the new coding scheme to be effective and propose two texture schemes incorporating countable elements, one consisting of lines and one of dot clusters. For comparison, we developed three alternative, color-based, coding schemes based on ideas previously expressed in the maritime community. Lastly, we present the design, dissemination, and results of an online user survey carried out to evaluate the five coding schemes. The survey results demonstrate that the proposed textures are the most preferred coding schemes among survey respondents.